Exploring genre classification in video game soundtracks: a case study of Barotrauma, DeadSpace, and Outlast - Abad, Mariana B.; Madril, Ariel M. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2024)
This study delves into the genre classification of horror, cyberpunk, and fantasy, examining their respective sonic elements. Through an analysis of selected tracks from the soundtracks of Barotrauma, DeadSpace, and Outlast, the study seeks to classify them within these genres. The analysis focuses on identifying key sonic features of each genre. Also, it explores the challenge of accurately attributing mickeymousing and leitmotivs within the context of the analyzed tracks, particularly in the absence of a comprehensive understanding of the game’s narrative. The findings shed light on the complexities of genre classification in video game music and highlight the importance of considering contextual factors in such analysis.